Design of Teaching Factory Practice Tools Concept, Perspective: Operation System on Solar Power Plant - Christina A. O. Kaseger; Stieven Netanel Rumokoy; Ali A. S. Ramschie; Stanley Bernadus Dodie (CCIT Journal, 2022)
Large-scale of solar power plants will continue to grow, especially in the tropical area. The increasing number of solar power plants required workers who have competence in operating these solar power plants. In order to prepare workers who have the ability to operate the solar power plants, prospective workers can be trained during the study period or in special training. The purpose of this research was to conceptualized the design of teaching factory practice tools concept by focused on the operating system of a solar power plant. The method used in this research, started with a literature study in order to obtained the information about the system requirements to be design. Then continued with the observation and interviews consecutively. In this study, the observation was made on the "XYZ" solar power plant with a capacity of 21MWp and interviewed to obtained information about the equipment and competencies was needed. Then the concept of a practical tools that meet the required competencies was designed using the Backward Chaining method. The results obtained was a concept design of the practical tools that can describe the operating conditions of a large-scale solar power plant based on Teaching Factory learning method.